Animated Mind-Mapping Media Based on Interactive Learning to Improve Digital Literacy and Collaboration Skills of Fifth Grade Elementary School Students - Komang Ayu Aprilia; I Wayan Widiana; Gede Wira Bayu (Universitas Pendidikan Ganesha, 2025)
This study was motivated by the low digital literacy and collaboration skills of fifth grade students. This research aims to develop learning media in the form of mind mapping animation based on interactive learning to improve digital literacy and collaboration skills of fifth grade students. The research uses the ADDIE model (analysis, design, development, implementation, evaluation). The subject of this research is animated mind mapping media based on interactive learning. The objects in this study are aspects of validity, practicality and effectiveness. The data collection method is questionnaire. The instrument to collect data is a questionnaire. The data analysis method used is the t-test formula. The results showed that: (1) the results of the validity of the material expert obtained a validity index of 0.98333, while the results of the validity of the media expert obtained a validity index of 0.97222, these results have very good qualifications, (2) the level of achievement of student responses obtained a score of 90.95% with very good qualifications, (3) the results of the correlated t-test showed a significance (2-tailed) of 0.000 or p < 0.05 so that the interactive learning-based mind mapping animation was effective in improving digital literacy and collaboration skills of grade V elementary school students. The implication of this research is the creation of interactive mind mapping animation learning media and provides insight for the development of innovative methods.